2021
DOI: 10.33225/jbse/21.20.204
|View full text |Cite
|
Sign up to set email alerts
|

Formative Assessment as a Tool to Enhance the Development of Inquiry Skills in Science Education

Abstract: Formative assessment (FA) is considered a powerful tool to enhance learning. However, there have been few studies addressing how the implementation of FA influences the development of inquiry skills so far. This research intends to determine the efficacy of teaching using FA in the development of students’ inquiry skills. A test of inquiry skills was used as the main research instrument to identify the level of the selected inquiry skills before and after a period of teaching with or without FA in the experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 63 publications
1
13
0
2
Order By: Relevance
“…Quite often, their subject is the effectiveness of formative assessment and the attitude of teachers towards its use in the educational process. For example, the results of the study Ganajova, Sotakova, Orosova (2021) prove the effectiveness of teaching science subjects using formative assessment. The following result of this study attracts attention: formative assessment stimulates learning of mainly those students who have lower academic performance compared to other students.…”
Section: Introductionmentioning
confidence: 77%
“…Quite often, their subject is the effectiveness of formative assessment and the attitude of teachers towards its use in the educational process. For example, the results of the study Ganajova, Sotakova, Orosova (2021) prove the effectiveness of teaching science subjects using formative assessment. The following result of this study attracts attention: formative assessment stimulates learning of mainly those students who have lower academic performance compared to other students.…”
Section: Introductionmentioning
confidence: 77%
“…Дослідження науковців та педагогічна практика дають підстави зробити висновок про цілу низку переваг цього методу. Наприклад, результати досліджень M. Ganajova et al (2021) та M. D. доводять ефективність навчання природничих предметів з використанням формувального оцінювання. За останні десятиліття формувальне оцінювання активно впроваджується у світі, зокрема в країнах ЄС, та набуває дедалі більшої ваги поряд з традиційними видами оцінювання і в Україні.…”
Section: вступunclassified
“…Afterward, the enhancement of formative assessment was related to the introduction of inquiry-based methods , and the realization of the two European FP7 projects: ESTABLISH (2010–2014) and SAILS (2012–2015) . Currently, there are several national projects that focus on the implementation of formative assessment in various school subjects, and this topic is spread across the country. , Orosová et al studied the status of assessment in Slovak schools in STEM. She concluded that teachers prefer using summative assessment over formative assessment.…”
Section: Research Backgroundmentioning
confidence: 99%